KAJIAN SIFAT FISIK KEDELAI VARITAS ANJASMORO DI DESA LOLAH KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Johsi R. Rawung; Lady C. Ch. E. Lengkey; Robert Molenaar (COCOS, 2023)
ABSTRACT The purpose of this study was to measure the dimensions of length, width, and thickness of soybean seeds at (two) different moisture content at 14% moisture content at harvest and 9% after drying, as well as determine the arithmetic diameter and geometry of soybean seeds, calculate the weight of 1000 soybean seeds in ( two) different moisture content, namely water content at harvest 14% and after drying 9%, calculating roundness, bulk angle and friction angle of soybean seeds at (two) different moisture content at water content at harvest 14% and after drying 9%, and determine the bulk angle and friction angle of soybean seeds at (two) different moisture content at 14% water content at harvest and 9% after drying. The research method was carried out by the experimental method. Data were collected on soybean seeds with 2 levels of moisture content, namely the water content after threshing (14%) and after drying (9%). From the results of this study, the average length, width, and thickness of soybean seeds of the Anjasmoro variety were soybean seeds at 9% moisture content, respectively 7.54 mm, 6.21 mm, 5.04 mm, and at water content 14% respectively 7.70 mm, 6.22 mm, 5.07 mm, obtained an average weight of 100 soybean seeds 16.10 g. The average weight of 1000 soybean seeds is 161 g, the bulk angle of soybean seeds at 9% moisture content ranges (23.2 – 25.4) with the average value of soybean seeds at 9% moisture content and 14% moisture content ranging from ( 19.25º). The lowest bulk angle of soybean seeds was at 9% and 14% moisture content (20.03º – 18.05º) with an average value of soybean seeds 9% and 14% (18.58º – 20.09º) and the highest bulk angle of soybean seeds was at moisture content 9% and 14% (23.01º – 23.00º) the average value of soybean seeds 9% and 14% (21.29º – 21.08º). The average friction angle of soybean seeds at 9% moisture content (14.10º) and the average soybean seed at 14% moisture content (17.01º).